Preparation method of aluminum oxide insulating coating of laser power meter applied to medical field
By using alumina insulating coating, combined with isopropanol cleaning, sandblasting, preheating and other processes, the shortcomings of existing insulating paints in terms of insulation effect, wear resistance and corrosion resistance are solved, and higher electrical insulation and heat resistance are achieved, and measurement accuracy and equipment reliability are improved.
Patent Information
- Application Number
- CN202510023321.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-11
AI Technical Summary
In the prior art, the high-temperature resistant insulating paint used by some manufacturers does not perform well in terms of insulation effect, wear resistance and corrosion resistance, and cannot effectively protect the substrate.
Alumina is used as the insulating coating material, and the alumina insulating coating is prepared through isopropanol cleaning, sandblasting of specific parameters, preheating, precision spraying, hole sealing, curing and grinding.
It improves the electrical insulation, heat resistance and wear resistance of the alumina coating, protects the measuring components from the external environment, and improves the measurement accuracy and equipment reliability.
Smart Images

Figure CN119800270A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of medical field, and in particular to a method for preparing an aluminum oxide insulating coating of a laser power meter used in the medical field. Background Art
[0002] The thin film thermopiles are distributed in a centrally symmetrical manner, and the thin film protective layer effectively prevents the thin film thermopiles from being affected by the environment, which may cause the detector accuracy to decrease. The IC circuit is used to receive, analyze, store and output test signals for subsequent processing system retrieval and application. When measuring continuous laser irradiation, the multi-layer thin film absorption layer converts the laser light energy into heat energy, which is then conducted through the thin film transition layer and the substrate and converted into electrical energy through the thin film thermopiles. The heat energy is processed by the IC circuit and then output, and finally a readable laser power value is obtained through the laser power meter display or the application display terminal.
[0003] Thermistor sensors convert photon energy into heat first, and then into current. Thermistor power sensors are based on the thermoelectric effect (also known as the Seebeck effect): when one end of a metal or alloy is heated, it releases electrons, and the electrons move toward the cooler end. This is a phenomenon that occurs as long as there is a temperature difference. It occurs between metals. The back of the product needs a coating with better insulation and stability to reduce current and temperature errors, increase reflectivity, and improve product accuracy. At present, most manufacturers use high-temperature resistant insulating paint, which has average insulation effect, poor wear resistance and corrosion resistance, and cannot protect the substrate.
[0004] The above information disclosed in this background technology is only used to increase the understanding of the background technology of the present invention and therefore, it may include information that does not constitute the prior art known to a person of ordinary skill in the art. Summary of the invention
[0005] In order to solve the problem that currently some manufacturers mostly use high temperature resistant insulating varnish, which has average insulation effect, poor wear resistance and corrosion resistance, and cannot protect the substrate, the present invention provides a method for preparing an aluminum oxide insulating coating for a laser power meter used in the medical field.
[0006] The present invention provides a method for preparing an aluminum oxide insulating coating for a laser power meter used in the medical field, which adopts the following technical solution:
[0007] A method for preparing an aluminum oxide insulating coating of a laser power meter used in the medical field, the method comprising the following steps:
[0008] Step 1: Before coating preparation, the product must first be cleaned with isopropyl alcohol.
[0009] Step 2: Sandblast the area of the product that needs to be sprayed, conduct three parameter tests, and finally select parameter a3 to sandblast the product.
[0010] The process test parameters for sandblasting in step 2 are as follows:
[0011] a1: Sand type: 80 white corundum, pressure 0.3MPa, sandblasting gun distance 300mm, sandblasting spacing 3mm, sand output 1400g / min, sandblasting angle 90°, roughness after sandblasting 5-6μm, flatness after sandblasting 0.04;
[0012] a2: Sand type: 100 white corundum, pressure 0.35MPa, sandblasting gun distance 200mm, sandblasting spacing 3mm, sand output 1400g / min, sandblasting angle 90°, roughness after sandblasting 4-5μm, flatness after sandblasting 0.02;
[0013] a3: Sand type: 80 white corundum, pressure 0.35MPa, sandblasting gun distance 200mm, sandblasting spacing 3mm, sand output 1400g / min, sandblasting angle 90°, roughness after sandblasting 7~8μm, flatness after sandblasting 0.05.
[0014] Step 3: After sandblasting, use compressed air to blow the surface clean to remove any remaining particles after sandblasting. Then, clean the surface with isopropyl alcohol to remove oil and other contaminants. After cleaning, wipe with a clean cloth to ensure that the surface is completely dry.
[0015] Step 4: Place the product in a preheating furnace for preheating. Usually, the temperature is set within a certain range and heated three times to ensure uniform temperature across the entire surface. Each heating time should be controlled within a reasonable range to avoid overheating and damage to the substrate.
[0016] Step 5: After determining the sandblasting parameters, the aluminum oxide coating is sprayed. Aluminum oxide powder with a purity of 99.9% is used as the coating material. The aluminum oxide powder is evenly sprayed on the surface of the product using a spraying device. To ensure the best effect, three spraying parameters are tested, and parameter b1 is finally selected for spraying;
[0017] The three spraying parameters in step 5 include the following:
[0018] b1: Powder type: 99.9% alumina powder, Ar42, H2:10, current 700A, powder output 30g / min, gun distance 100mm, spacing 3mm, coating thickness 200-300μm, impedance 509GΩ, adhesion 13.84MPa, porosity 2%;
[0019] b2: Powder type: 99.9% alumina powder, Ar46, H2:8, current 700A, powder output 26g / min, gun distance 100mm, spacing 3mm, coating thickness 200-300μm, impedance 213GΩ, adhesion 10.09MPa, porosity 7%;
[0020] b3: Powder type: 99.9% alumina powder, Ar46, H2:10, current 700A, powder output 26g / min, gun distance 100mm, spacing 3mm, coating thickness 200-300μm, impedance 414GΩ, adhesion 8.74MPa, porosity 5%.
[0021] Step 6: Use epoxy resin glue to seal the holes and apply it evenly on the coating surface;
[0022] Step 7: Place the product in an oven for curing;
[0023] Step 8: Use precision grinding equipment to grind the coating surface to the specified thickness range.
[0024] Step 9: After production is completed, conduct voltage resistance test, resistance test, porosity test, and pull-out force test.
[0025] Preferably, step 6 comprises:
[0026] During processing, place the product at 30°C for 8 hours to ensure that the glue is completely cured. After curing, wipe with propanol to remove excess glue on the surface.
[0027] Preferably, the curing temperature in step 7 is 140° C. and the curing time is 8 hours.
[0028] Preferably, the specified thickness range of the coating surface grinding in step 8 is 100-200 um, and the surface roughness (Ra value) is less than 1 μm.
[0029] Preferably, the test results in step 9 are as follows:
[0030] Voltage Withstand Test: The coating is subjected to a 3KV high voltage test to confirm that it has good voltage withstand capability and passes the test;
[0031] Resistance test: The resistance value was 509GΩ after resistance test, indicating that the electrical insulation of the coating was good;
[0032] Porosity test: The porosity of the coating was tested and the result was 2.4%, indicating that the coating had good density and few pores;
[0033] Pull-out force test: The pull-out force between the coating and the substrate was tested, and the result was 13.84 MPa, indicating that the coating has good adhesion to the substrate and can withstand greater mechanical stress.
[0034] In summary, the present invention includes the following beneficial technical effects:
[0035] This application uses a series of operations such as isopropyl alcohol cleaning, specific parameter sandblasting, preheating, precision spraying, sealing, curing, grinding and comprehensive testing to effectively remove oil, dust and other pollutants on the product surface and form a suitable roughness to enhance the adhesion of the aluminum oxide coating. It accurately controls parameters such as coating thickness, impedance, porosity, etc., so that the electrical insulation, heat resistance and wear resistance of the aluminum oxide coating are stronger than the original high-temperature insulating paint, protecting the measuring elements from external environmental influences such as humidity, dust and corrosive gases, thereby improving the measurement accuracy and reliability of the equipment, and performing well in withstand voltage, resistance, porosity and pull-out force tests, ensuring that the coating quality of products such as thermistor elements is excellent, the performance is stable and reliable, meets the requirements of special environmental use and extends the service life of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a graph showing the porosity detection results of the sandblasting treatment in step 9 of the embodiment of the invention. DETAILED DESCRIPTION
[0037] The following is combined with Figure 1 The present invention is described in further detail.
[0038] The embodiment of the present invention discloses a method for preparing an aluminum oxide insulating coating of a laser power meter used in the medical field. Figure 1 The method for preparing the aluminum oxide insulating coating of the laser power meter comprises the following steps:
[0039] Step 1: Before coating preparation, the product must first be cleaned with isopropyl alcohol. Pour the isopropyl alcohol into a cleaning container, dip a non-woven fabric or clean flannel into the isopropyl alcohol, and gently wipe the surface of the product, especially the spraying area and small parts. Ultrasonic cleaning can be performed if necessary to ensure thorough cleaning. As a common solvent, isopropyl alcohol can effectively remove oil, dust and other contaminants on the surface. The cleaning process should ensure that the product surface is clean and free of any residue to ensure the smooth progress of subsequent processes and avoid affecting the adhesion of the coating.
[0040] Step 2: Sandblast the area where the product needs to be sprayed. The purpose of sandblasting is to increase the adhesion of the aluminum oxide coating to the substrate by roughening the surface of the product. The micron-level roughness formed on the surface after sandblasting will help the coating to adhere better. Three parameter tests were conducted, and parameter a3 was finally selected to sandblast the product. The rough surface provides more attachment points for the coating, allowing the coating to be better embedded in the surface of the substrate, thereby enhancing the bonding between the coating and the substrate, reducing the risk of coating peeling or peeling, and extending the service life of the product. It is especially suitable for products such as thermal probe components that require high coating adhesion.
[0041] In this application, the process test parameters for sandblasting in step 2 are as follows:
[0042] a1: Sand type: 80 white corundum, pressure 0.3MPa, sandblasting gun distance 300mm, sandblasting spacing 3mm, sand output 1400g / min, sandblasting angle 90°, roughness after sandblasting 5-6μm, flatness after sandblasting 0.04;
[0043] a2: Sand type: 100 white corundum, pressure 0.35MPa, sandblasting gun distance 200mm, sandblasting spacing 3mm, sand output 1400g / min, sandblasting angle 90°, roughness after sandblasting 4-5μm, flatness after sandblasting 0.02;
[0044] a3: Sand type: 80 white corundum, pressure 0.35MPa, sandblasting gun distance 200mm, sandblasting spacing 3mm, sand output 1400g / min, sandblasting angle 90°, roughness after sandblasting 7~8μm, flatness after sandblasting 0.05.
[0045] Step 3: After sandblasting, use compressed air to blow the surface clean to remove any remaining particles after sandblasting. Then, clean the surface with isopropyl alcohol to remove oil and other contaminants. After cleaning, wipe with a clean cloth to ensure that the surface is completely dry.
[0046] Step 4: Place the product in a preheating furnace for preheating. Usually, the temperature is set within a certain range and heated three times to ensure uniform temperature over the entire surface. Each heating time should be controlled within a reasonable range to avoid overheating and damage to the substrate. This process helps remove surface moisture and ensures uniform adhesion of the coating. In the thermal probe element, a uniform coating can ensure that its temperature sensing and conduction performance is the same in different parts, improving the accuracy and reliability of the product.
[0047] Step 5: After determining the sandblasting parameters, the next step is to spray the aluminum oxide coating. Use 99.9% pure aluminum oxide powder as the coating material. The spraying thickness is usually controlled between 200 and 300 microns. Aluminum oxide has good high temperature resistance and insulation properties, and is an ideal coating material for thermal probe components. Use spraying equipment to evenly spray aluminum oxide powder on the product surface. During the spraying process, the thickness and uniformity of the spraying need to be controlled to avoid missing or too thick a coating that affects performance. To ensure the best effect, three spraying parameters are tested, and finally parameter b1 is selected for spraying.
[0048] In this application, the three spraying parameters in step 5 include the following:
[0049] b1: Powder type: 99.9% alumina powder, Ar42, H2:10, current 700A, powder output 30g / min, gun distance 100mm, spacing 3mm, coating thickness 200-300μm, impedance 509GΩ, adhesion 13.84MPa, porosity 2%;
[0050] b2: Powder type: 99.9% alumina powder, Ar46, H2:8, current 700A, powder output 26g / min, gun distance 100mm, spacing 3mm, coating thickness 200-300μm, impedance 213GΩ, adhesion 10.09MPa, porosity 7%;
[0051] b3: Powder type: 99.9% alumina powder, Ar46, H2:10, current 700A, powder output 26g / min, gun distance 100mm, spacing 3mm, coating thickness 200-300μm, impedance 414GΩ, adhesion 8.74MPa, porosity 5%.
[0052] In this application, the appropriate coating thickness can meet the insulation and high temperature resistance requirements of the thermistor element, while good impedance and low porosity ensure the electrical insulation and density of the coating, preventing external factors from corroding and interfering with the internal structure of the product. High adhesion further ensures that the coating will not fall off easily during use, thereby ensuring the long-term stability and reliability of the product.
[0053] Step 6: Use epoxy resin glue to seal the holes and apply it evenly on the coating surface;
[0054] In this application, step 6 includes: during processing, place the product at 30°C for 8 hours to ensure that the glue is completely cured. After curing, wipe the excess glue on the surface with propanol to avoid glue residue affecting the quality of the coating. For the thermal probe element, it can better prevent impurities such as moisture and gas from penetrating into the coating, thereby protecting the substrate from corrosion. It also helps to maintain the insulation and high temperature resistance of the coating, and enhance the product's ability to be used in harsh environments.
[0055] Step 7: Place the product in an oven for curing. The curing temperature in step 7 is 140°C and the curing time is 8 hours. High-temperature curing can promote the cross-linking reaction between the coating molecules, enhance the hardness, wear resistance and chemical corrosion resistance of the coating, and make the coating more durable. The stable coating can keep the performance of the thermal probe element unchanged in a long-term high-temperature environment, ensuring the reliability and accuracy of the product.
[0056] Step 8: Use a precision grinding device, a gantry machine tool 800 grinding wheel, to grind the coating surface to a specified thickness range for finishing. The specified thickness range of the coating surface grinding in step 8 is 100 to 200 μm, and the surface roughness (Ra value) is less than 1 μm.
[0057] Step 9: After production is completed, conduct voltage resistance test, resistance test, porosity test, and pull-out force test.
[0058] like Figure 1 As shown, the test results in step 9 are as follows:
[0059] Voltage Withstand Test: The coating is subjected to a 3KV high voltage test to confirm that it has good voltage withstand capability and passes the test;
[0060] Resistance test: The resistance value was 509GΩ after resistance test, indicating that the electrical insulation of the coating was good;
[0061] Porosity test: The porosity of the coating was tested and the result was 2.4%, indicating that the coating had good density and few pores;
[0062] Pull-out force test: The pull-out force between the coating and the substrate was tested, and the result was 13.84 MPa, indicating that the coating has good adhesion to the substrate and can withstand greater mechanical stress.
[0063] In this application, after the production is completed, the withstand voltage, resistance test, porosity test and pull-out force test are carried out, and the test results show that the product quality is excellent. The withstand voltage test (3KV high voltage test) proves that the coating has good withstand voltage capability and can work normally under high voltage environment; the resistance value is 509GΩ, which shows excellent electrical insulation and can effectively prevent current leakage; the porosity is 2.4%, which shows that the coating has good density and can effectively block the invasion of foreign substances; the pull-out force test result is 13.84MPa, which proves that the coating has strong adhesion to the substrate and can withstand greater mechanical stress. Through these comprehensive tests, it can ensure that the product meets the performance requirements of thermistor probe components, ensure the safety, reliability and stability of the product in practical applications, and improve the market competitiveness of the product.
[0064] Finally, a few points should be explained: First, in the description of the present invention, it should be noted that, unless otherwise specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, which may refer to mechanical connection or electrical connection, or internal communication between two components, or direct connection. "upper", "lower", "left", "right", etc. are only used to indicate relative positional relationships. When the absolute position of the object being described changes, the relative positional relationship may change;
[0065] Secondly: In the drawings of the embodiments disclosed in the present invention, only the structures related to the embodiments disclosed in the present invention are involved, and other structures can refer to the general design. In the absence of conflict, the same embodiment and different embodiments of the present invention can be combined with each other;
[0066] Finally: The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
[0067] The above are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an aluminum oxide insulating coating for a laser power meter used in the medical field, characterized in that: The method for preparing the aluminum oxide insulating coating of the laser power meter comprises the following steps: Step 1: Before coating preparation, first clean the product with isopropyl alcohol; Step 2: Sandblast the area of the product that needs to be sprayed, conduct three parameter tests, and finally select parameter a3 to sandblast the product; Step 3: Use compressed air to blow the surface clean to remove any particles left after sandblasting. Then, clean the surface with isopropyl alcohol to remove oil and other dirt. After cleaning, wipe with a clean cloth to ensure that the surface is completely dry. Step 4: Place the product in a preheating furnace for preheating treatment, and heat it three times to ensure that the temperature of the entire surface is uniform; Step 5: After determining the sandblasting parameters, the aluminum oxide coating is sprayed. Aluminum oxide powder with a purity of 99.9% is used as the coating material. The aluminum oxide powder is evenly sprayed on the surface of the product using a spraying device. To ensure the best effect, three spraying parameters are tested, and parameter b1 is finally selected for spraying; Step 6: Use epoxy resin glue to seal the holes and apply it evenly on the coating surface; Step 7: Place the product in an oven for curing; Step 8: Use precision grinding equipment to grind the coating surface to the specified thickness range; Step 9: After production is completed, conduct voltage resistance test, resistance test, porosity test, and pull-out force test.
2. The method for preparing an aluminum oxide insulating coating for a laser power meter used in the medical field according to claim 1, characterized in that: The process test parameters of the sandblasting treatment in step 2 are as follows: a1: Sand type: 80 white corundum, pressure 0.3MPa, sandblasting gun distance 300mm, sandblasting spacing 3mm, sand output 1400g / min, sandblasting angle 90°, roughness after sandblasting 5-6μm, flatness after sandblasting 0.04; a2: Sand type: 100 white corundum, pressure 0.35MPa, sandblasting gun distance 200mm, sandblasting spacing 3mm, sand output 1400g / min, sandblasting angle 90°, roughness after sandblasting 4-5μm, flatness after sandblasting 0.02; a3: Sand type: 80 white corundum, pressure 0.35MPa, sandblasting gun distance 200mm, sandblasting spacing 3mm, sand output 1400g / min, sandblasting angle 90°, roughness after sandblasting 7~8μm, flatness after sandblasting 0.
05.
3. The method for preparing an aluminum oxide insulating coating for a laser power meter used in the medical field according to claim 1, characterized in that: The three spraying parameters in step 5 include the following: b1: Powder type: 99.9% alumina powder, Ar42, H2:10, current 700A, powder output 30g / min, gun distance 100mm, spacing 3mm, coating thickness 200-300μm, impedance 509GΩ, adhesion 13.84MPa, porosity 2%; b2: Powder type: 99.9% alumina powder, Ar46, H2:8, current 700A, powder output 26g / min, gun distance 100mm, spacing 3mm, coating thickness 200-300μm, impedance 213GΩ, adhesion 10.09MPa, porosity 7%; b3: Powder type: 99.9% alumina powder, Ar46, H2:10, current 700A, powder output 26g / min, gun distance 100mm, spacing 3mm, coating thickness 200-300μm, impedance 414GΩ, adhesion 8.74MPa, porosity 5%.
4. The method for preparing an aluminum oxide insulating coating for a laser power meter used in the medical field according to claim 1, characterized in that: The step 6 comprises: During processing, place the product at 30°C for 8 hours to ensure that the glue is completely cured. After curing, wipe with propanol to remove excess glue on the surface.
5. The method for preparing an aluminum oxide insulating coating for a laser power meter used in the medical field according to claim 1, characterized in that: The curing temperature in step 7 is 140° C. and the curing time is 8 hours.
6. The method for preparing an aluminum oxide insulating coating for a laser power meter used in the medical field according to claim 1, characterized in that: The specified thickness range of the coating surface grinding in step 8 is 100-200 um, and the surface roughness (Ra value) is less than 1 μm.
7. The method for preparing an aluminum oxide insulating coating for a laser power meter used in the medical field according to claim 1, characterized in that: The test results in step 9 are as follows: Withstand voltage test: The coating was subjected to a 3KV high voltage test and passed the test; Resistance test: passed the resistance test, the resistance value is 509GΩ; Porosity test: The porosity of the coating was tested and the result was 2.4%; Pull-out force test: The pull-out force between the coating and the substrate was tested, and the result was 13.84 MPa.
Citation Information
Cited By
Cable manufacturing device
CN120913970A